2012
DOI: 10.1002/marc.201200011
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Polymer Coatings: A General Route to Thiol‐ene and Thiol‐yne Click Reactions

Abstract: Reactive polymer coatings were synthesized via chemical vapor deposition (CVD) polymerization process. These coatings decouple surface design from bulk properties of underlying materials and provide a facile and general route to support thiol-ene and thiol-yne reactions on a variety of substrate materials. Through the reported technique, surface functions can be activated through a simple design of thiol-terminated molecules such as polyethylene glycols (PEGs) or peptides (GRGDYC), and the according biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 63 publications
2
46
0
1
Order By: Relevance
“…In 2012, Wu et al created UV lithography based patterning of alkene and alkyne‐functionalized polymers on various substrates via TEC and TYC reactions . In another study of modification of polymer surfaces published in 2012, Norberg et al produced lectin sensors by utilizing TEC and TYC reactions of thiolated carbohydrates on alkene and alkyne‐functionalized polystyrene .…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, Wu et al created UV lithography based patterning of alkene and alkyne‐functionalized polymers on various substrates via TEC and TYC reactions . In another study of modification of polymer surfaces published in 2012, Norberg et al produced lectin sensors by utilizing TEC and TYC reactions of thiolated carbohydrates on alkene and alkyne‐functionalized polystyrene .…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that this last chemical modification pathway was more efficient and controllable, allowing an efficient functionalization of cellulose films. Wu and co‐workers reported an approach for facilitating both thiol‐ene and thiol‐yne surface modification with alkene and alkyne functionalized polymers deposited on a variety of substrates, including gold, polystyrene, glass, titanium, and polydimethylsiloxane . The required polymers, poly(4‐vinyl‐ p ‐xylylene‐ co ‐ p ‐xylylene) and poly(4‐ethynyl‐ p ‐xylylene‐ co ‐ p ‐xylylene), were prepared via chemical vapour deposition (CVD) polymerization of 4‐vinyl‐[2.2]paracyclophane and ethynyl‐[2.2]paracyclophane on the solid support.…”
Section: Thiol‐ene Click Reactionsmentioning
confidence: 99%
“…Fujisawa et al [10] established a procedure for grafting thiol functionalities on the hydroxyl groups located at the surface of carbon fibers, again with the use of thiirane, and confirmed the transfer agent property of the thiol groups that were grafted, in the case of the polymerization of styrene initiated by a peroxide. More generally, the thiol-ene "click" reaction has attracted attention recently for the functionalization of surfaces destined to biological applications [11] and for the synthesis of polymers [12]. But, to the best of our knowledge, a quantified evaluation of the efficiency of this strategy as a mean of improving interfacial adhesion has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%